Stretchable Batteries: Stand‐Alone Intrinsically Stretchable Electronic Device Platform Powered by Stretchable Rechargeable Battery (Adv. Funct. Mater. 50/2020). (8th December 2020) - Song, Woo‐Jin; Kong, Minsik; Cho, Sunghwan; Lee, Sangyeop; Kwon, Jimin; Son, Hye Bin; Song, Jun Hyuk; Lee, Dong‐Gue; Song, Gyujin; Lee, Sang‐Young; Jung, Sungjune; Park, Soojin; et al.
Abstract : In article number 2003608, Soojin Park, Unyong Jeong, and co‐workers propose an intrinsically stretchable electronic device platform powered by a stretchable film battery. The rechargeable battery is used as a substrate on which a stretchable circuit board is printed. This device platform opens the possibility of fabricating fully stand‐alone stretchable devices and integrated miniaturized devices.